3D printing of carbon nanotubes reinforced thermoplastic polyimide composites with controllable mechanical and electrical performance. (29th September 2019) - Ye, Wenli; Wu, Wenzheng; Hu, Xue; Lin, Guoqiang; Guo, Jinyu; Qu, Han; Zhao, Ji
Abstract: Existing aerospace metal parts or structural parts have the problems of finite elasticity, large mass, difficult manufacture of complex parts, expensive equipment, narrow range of shielding and electrostatic regulation. This study analyzed the tensile and bending properties of pure thermoplastic polyimide (TPI) 3D printing specimens printed by the nozzles with different diameters. The effects of different carbon nanotube (CNT) contents on the thermal and electrical properties of carbon nanotube composites were investigated. The relationship between the electrical conductivity, tensile properties, bending properties, resistivity and cyclic bending deformation of 3D printed specimens with different carbon nanotube contents was studied. Compared with the 0.4 mm nozzle, the tensile and bending strength of pure TPI specimen printed by a 0.8 mm nozzle were increased by 40% and 20%, respectively. In order to ensure the excellent mechanical and electrical properties of 3D printed composites, 3%wt carbon nanotubes-thermoplastic polyimide (CNTs-TPI) composites with appropriate tensile and bending strength were used to print the characteristic structure, and then the relationship between the deformation and conductive resistance was studied. By optimizing the 3D printing parameters and the filling contents of CNTs, it is possible to print complex parts which can be used in aerospace and industrial fields with special properties, such as electrical conductivity, mechanical properties, temperature resistance and anti-electromagnetic shielding.